Comparison of DNA Extraction Methods for Microbial Community Analysis in Indonesian Tempe Employing Amplified Ribosomal Intergenic Spacer Analysis - CECILIA ANNA SEUMAHU; ANTONIUS SUWANTO; IMAN RUSMANA; DEDY DURYADI SOLIHIN (Bogor Agricultural University, Indonesia, 2012)
Tempe fermentation involved complex microbial communities which are only revealed partially through culture dependent methods. Culture-independent methods would be potential to unravel this complex microbial fermentation. Appropriate DNA extraction is an essential tool to obtain reliable data from culture independent method. In this study, we employed two commercial DNA extraction methods to find the best one for microbial community characterization employing amplified ribosomal intergenic spacer analysis (ARISA). Our result showed that PowerFood Microbial DNA Isolation Kit-MOBIO (PFMDIK) is an excellent method for microbial DNA extraction from tempe. It gave high quantity and quality of DNA suitable for PCR amplification of 16S-23S rRNA intergenic spacer to yield a diverse and reproducible ARISA profile.